Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Hastings Dean Mary Kay Kane speaking with Judge Annette LaRue looking on Luncheon held at the Downtown Club